PENDEKATAN PEMBELAJARAN BAHASA WHOLE LANGUAGE - HIDAYAH, NURUL (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
Whole language approach is one approach to language learning. Whole language approach is based on the concept konsrtuktivisme, language experience approcah (LEA) in education. In this approach determines the language as learning materials, learning content and learning process. In applying the whole languageguru know and understand the components of the whole languageagar pembelajarn be done optimally. Components in the whole language there are 8 alound reading, journal writing, sustained silent reading, shared reading, guided reading, guided writing, independent reading, and independent writing.